Facts or Fiction? : the Church of Ireland's writting of Irish church history 1838-1870 - Blake Knox, Jamie (Trinity College (Dublin, Ireland). Department of History, 2014)
This thesis explores a central, but curiously neglected dimension of the cultural and intellectual history of Ireland in the nineteenth century. It addresses the systematic attempt by a group of scholars and academics, largely based in Trinity College, Dublin, to re-write the history of the Irish Church. Their preoccupation with the historical origins of their Church was shared with English Episcopalians. In both cases, academics and theologians sought justification for the birth of their respective Reformed branches of Christianity.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin